2022
DOI: 10.1186/s43019-022-00137-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery for major orthopedic surgery: a narrative review

Abstract: Background With increasing interest in enhanced recovery after surgery (ERAS), the literature on ERAS in orthopedic surgery is also rapidly accumulating. This review article aims to (1) summarize the components of the ERAS protocol applied to orthopedic surgery, (2) evaluate the outcomes of ERAS in orthopedic surgery, and (3) suggest practical strategies to implement the ERAS protocol successfully. Main body Overall, 17 components constituting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 120 publications
1
23
1
Order By: Relevance
“…In these RCTs, patient education and pre-emptive anesthetics and analgesics were the main pre-operative ERAS elements. A preoperative ERAS element of key importance little considered in these studies was the nutritional status [ 196 ]. in only two RCTs, it was reported that carbohydrate loading with a clear carbohydrate liquid 2 h prior to surgery was used in order to present the patient to surgery in a metabolically fed state leading to less postoperative protein loss and preservation of muscle mass [ 196 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In these RCTs, patient education and pre-emptive anesthetics and analgesics were the main pre-operative ERAS elements. A preoperative ERAS element of key importance little considered in these studies was the nutritional status [ 196 ]. in only two RCTs, it was reported that carbohydrate loading with a clear carbohydrate liquid 2 h prior to surgery was used in order to present the patient to surgery in a metabolically fed state leading to less postoperative protein loss and preservation of muscle mass [ 196 ].…”
Section: Discussionmentioning
confidence: 99%
“…A preoperative ERAS element of key importance little considered in these studies was the nutritional status [ 196 ]. in only two RCTs, it was reported that carbohydrate loading with a clear carbohydrate liquid 2 h prior to surgery was used in order to present the patient to surgery in a metabolically fed state leading to less postoperative protein loss and preservation of muscle mass [ 196 ]. This is probably due to the fact that this ERAS element requires special attention for those patients with specific comorbidities, such as obesity and diabetes, pathological conditions more common in aged patients [ 196 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations